Die metodiek en aanwendingsmoontlikhede van 'n markprysbepalingsmetode by onduursame verbruikersgoedere - Chris P. Lerm (South African Journal of Business Management, 1982)
– The methodology and applicability of a method to determine the market price of non-durable consumer products Proper pricing should be done in three phases. Firstly, the determination of the market price, namely that price which the consumers are prepared to pay for the amount of need-satisfaction they perceive from using the product. Secondly, the determination of the target price, namely that price which will give a satisfactory rate of return on investment for the firm. Thirdly, the determination of the final price, by achieving a match between the market price and the target price. The present methods to determine the market price were analysed and with this information a new method to determine the market price of non-durable consumer products was developed. The objectives of this article are to report on an empirical investigation undertaken to test the feasibility of this method and the seven steps to follow in using the method; and to outline the results obtained and conclusions which may be reached; the implications and use of the empirical data; and the method to determine the market price.
Keywords: 650